Hydrogeochemical characteristic and recognization of saline groundwater formation and evolution in silty coast of the Yellow Sea and Bohai Sea, Eastern China - Gao, Maosheng; Sun, Qiming; Dang, Xianzhang; Hou, Guohua; Guo, Fei; Liu, Zhenlin; Chang, Xinyue; Zhao, Guangming (Frontiers in Earth Science, 2023)
Saline groundwater is a valuable unconventional water resource in silty coastal zone, which contain complex and fragile sedimentary and hydrological environments that are widely distributed and vulnerable to human activities. Coastal groundwater salinization along the eastern coast of China since the late Pleistocene is thought to be a response to global environmental change. Previous studies have shown a spatial and temporal link between the development of saline groundwater and deposition of marine strata. However, groundwater salinization is becoming an increasing problem in coastal zone, and the hydrogeochemical characteristics and cause of the groundwater salinization or desalinization remain poorly understood. In this study, we compared the hydrogeochemical characteristics and relationships between saline groundwater and the sedimentary environment in two representative, muddy coastal zone of the Yellow Sea coast (YSC) and Bohai Sea coast (BSC). Our monitoring results show that the groundwater varies from fresh water, to brackish water, saltwater, and brine moving offshore of the BSC, with total dissolved solid (TDS) concentrations of 203–184,196 mg/L. In contrast, brine is absent from the YSC, where the TDS concentrations range from 280 to 41,690 mg/L. The relationships between δ2H and δ18O values indicate that freshwater–seawater–brine and freshwater–seawater mixing are the main processes leading to enrichment in TDS in the BSC and YSC, respectively. Based on the relationship between the major cations, Cl−, and Cl/Br ratios, the results show that the groundwater salinity is primarily due to saltwater intrusion and secondly to water–rock interactions (i.e., evaporitic salt dissolution and cation exchange). The regression curves on plots of Na–Cl and (Ca+Mg)–(CO3+SO4) have negative slopes (−0.33 and −0.34, respectively) for the groundwater samples from the BSC and YSC, indicating the Na in groundwater exchange for Ca due to seawater or residual seawater intrusion. The saline groundwater (or brine) samples with reverse ion exchange indicate that seawater or residual seawater has invaded the aquifer, and in which Na+ is replacing Ca2+ and Mg2+. These results enhance our understanding of the formation and evolution of saline groundwater, and provide insights into groundwaters in other silty coastal zones.